Pengaruh Profitabilitas, Leverage, Likuiditas, Ukuran Perusahaan Dan Struktur Aset Terhadap Nilai Perusahaan - Febri Indra Farizki; Suhendro Suhendro; Endang Masitoh (Ekonomis: Journal of Economics and Business, 2021)
This research aims to examine and analyze the impact of profitability, leverage, liquidity, company size and asset structure on firm value in the company of sub-sector property and real estate listed on the Stock Exchange Indonesia period in 2015-2019. The population of this research is the entire property and real estate sub-sector companies listed on the IDX. The sampel selection in this research using purposive sampling with certain criteria thus obtained 38 samples of data to be researched. The data used are secondary obtained from financial report. The analysis technique used multiple linear regression analysis. The results showed that liquidity, company size, and asset structure affect on firm value. Meanwhile profitability and leverage do not affect on firm value in the company sub-sector property and real estate period 2015-2019